Homoarginine: a prognostic indicator in adolescents and adults with complex congenital heart disease? - Rädle-Hurst, Tanja; März, Winfried (PLOS ONE, 2017)
Background: Homoarginine (hArg) has been shown to be of prognostic value in patients with chronic left heart failure. The present study aims to assess the clinical utility and prognostic value of hArg levels in patients with complex congenital heart disease (CHD). Methods: Plasma hArg levels were measured in 143 patients with complex CHD and compared to clinical status, echocardiographic and laboratory parameters as well as the occurrence of adverse cardiac events. Results: Median hArg levels were 1.5 μmol/l in CHD patients as compared to 1.70 μmol/l in healthy controls (p = 0.051). Median hArg levels were lowest in patients with Fontan palliation (1.27 μmol/l) and Eisenmenger physiology (0.99 μmol/l) and decreased with the severity of adverse cardiac events with lowest values found in patients prior to death or overt heart failure (0.89 μmol/l). According to ROC analysis, the most important predictors of adverse cardiac events were hArg levels (AUC 0.837, p<0.001, CI 0.726-0.947), NYHA class (AUC 0.800, p<0.001, CI 0.672-0.928) and NT-proBNP levels (AUC 0.780, p<0.001, CI 0.669-0.891). The occurrence of overt heart failure or death due to progressive heart failure were best predicted by NYHA class (AUC 0.945, p<0.001, CI 0.898-0.992), hArg levels (AUC 0.911, p<0.001, CI 0.850-0.971) and NT-proBNP levels (AUC 0.877, p<0.001, CI 0.791-0.962), respectively. Conclusion In patients with complex CHD, hArg levels can predict adverse cardiac events as reliably as or even better than NT-proBNP levels and thus might be of prognostic value in this subset of patients.